Understanding the Impact of Customer Perceived Value on Hotel Customers’ Satisfaction: A Systematic Literature Review - Ghani, Amanina Mat; Kamarudin, Wan Nor Bayah Wan; Isa, Sulaiha Mohd; Abas, Siti Aisah; Ghazali, Ameleya Muhammad (Information Management and Business Review, 2025)
In the rapidly growing and competitive hotel industry, customer satisfaction is vital for ensuring success, and one of the key factors influencing satisfaction is perceived value. This study investigates how customer perceived value (CPV) impacts customer satisfaction within the hotel industry. Recognizing the importance of CPV in crafting memorable interactions, this study adapts the PRISMA method (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) to collect and analyze relevant articles through established online databases from 2014 to 2024. Approximately 20 qualifying studies from various academic databases were chosen, offering valuable insight into research on CPV within the hotel industry. The findings highlight the impacts of CPV, such as functional, emotional, and social, that significantly influence customer satisfaction in the hotel industry. Despite limited studies, the findings indicate that CPV can dramatically improve customer experiences and loyalty. Industry practitioners should also design value-driven strategies that enhance functional, emotional, and social value while ensuring competitive advantages. For academic researchers, it proposes further exploration into under-explored areas of CPV within hotel services. By incorporating these insights, scholars and industry professionals may improve overall customer satisfaction in the increasingly competitive hotel industry.